1989
DOI: 10.1152/jappl.1989.66.4.1561
|View full text |Cite
|
Sign up to set email alerts
|

Different hematologic responses to hypoxia in Sherpas and Quechua Indians

Abstract: Previous studies of the erythropoietic response to hypoxia in high-altitude natives suggest that the hematocrit and hemoglobin values in Himalayan natives (Sherpas) are lower than expected for the altitude, perhaps because of a genetic adaptation. However, differences in sampling techniques and experimental methods make comparisons difficult. Our studies were carried out to compare the erythropoietic response with the same altitude in age-matched natives of the Himalayas and Andes by the same experimental tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
87
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(97 citation statements)
references
References 0 publications
8
87
1
Order By: Relevance
“…As with the instances above of acclimatized lowlanders, the similarity between the P 50 values of the high altitude natives and sea level controls was attributed to an in vivo balance of the influences of alkalosis and increased [2,3-DPG] on the affinity of Hb for O 2 . A later study by Winslow et al (1989) showed similar results in a group of high altitude Sherpas living at 3700 m, whose physiological ODCs were not shifted as compared to controls.…”
Section: Previous Studies In Lowlanders and Native Highlanders At Higmentioning
confidence: 53%
“…As with the instances above of acclimatized lowlanders, the similarity between the P 50 values of the high altitude natives and sea level controls was attributed to an in vivo balance of the influences of alkalosis and increased [2,3-DPG] on the affinity of Hb for O 2 . A later study by Winslow et al (1989) showed similar results in a group of high altitude Sherpas living at 3700 m, whose physiological ODCs were not shifted as compared to controls.…”
Section: Previous Studies In Lowlanders and Native Highlanders At Higmentioning
confidence: 53%
“…The studies by Beall et al (Beall et al, 2010) and Yi et al (Yi et al, 2010) revealed a striking signal of positive selection at EPAS1, and documented that noncoding nucleotide variants in and around the EPAS1 gene are strongly associated with a reduced Hb concentration in Tibetan highlanders. Previous studies demonstrated that Tibetan highlanders are characterized by low Hb concentrations relative to acclimatized lowlanders, as well as to Andean highlanders that are resident at comparable altitudes (Beall and Reichsman, 1984;Winslow et al, 1989;Beall et al, 1990;Beall et al, 1998;Garruto et al, 2003;Wu et al, 2005;Beall, 2007). Remarkably, Tibetans living at elevations of up to 4000m present a hematological profile similar to what would be expected at sea level.…”
Section: Tissue O 2 Utilizationmentioning
confidence: 77%
“…Typically, Tibetans average at least 1 g/dL and as much as approximately 3.5 gm/dL (i.e. approximately 10-20%) lower hemoglobin concentration in comparison with their Andean counterparts (14)(15)(16) or acclimatized lowlanders, such as the Han who have moved to altitudes above 2,500 m (4,(17)(18)(19)(20)(21)(22)(23). This suggests that Tibetans have evolved a blunted erythropoietic response to high-altitude hypoxia.…”
mentioning
confidence: 99%